Plant cell biology : - Gunning, Brian E.S. (Jones and Bartlett Publishers, 1996)
Contents: Microscopy of plant cells; nucleus; vacuoles; mitochondria; nucleic acids in mitochondria and plastids; plant reproduction; the plant as a multicellular organism.